Authorship attribution and statistical text analysis - Modaber Dabagh, Rohangiz (Metodološki zvezki, 2007)
In the study of ancient literature, a major problem is to deal with uncertain authorship. Ambiguity about authorship is not limited to the works from remote era. Different reasons cause uncertainty in authorship, such as reproduction of books by hand, prestige, having good sells for works with forged reputable names on them, and sometimes social or political pressures. Whatever the reason, authorship case studies offer the statistician an interesting opportunity to deal with various applied problems, where many standard statistical techniques have been introduced. In statistical analysis of literary texts one tries to apply an objective methodology to works that have received impressionistic treatment for a long time. In subjective analysis of literary style, experts use literary style of the text, which is not quantifiable, as an important criterion in their judgments. Subjective approach can rarely lead to a unique solution acceptable to all the scholars. Statistical quantitative methods provide objective components for judgments. In the quantitative approach, by carefully analyzing the style of the text one tries to find out how to characterize the style of an author numerically and determine sets of features (variables) in a text that most accurately describe the author's style. Much work has been done covering different aspects of this field. Different variables are proposed as distinguishing characteristics of writers, a wide range of mathematical methods is employed, and there is still a lot to be done in the future. The paper presents a brief history and a review of the statistical analysis of literary style, looks at several variables that have been used as stylistic criteria of authors, as well as the methods used. This is followed by some illustrations on Farsi text, implying that there are some general rules that hold for different languages.
Keywords: Statistical analysis; Statistična analiza; Tekstualna analiza; Text analysis; Literarni stili; Literary styles; Authorship; Avtorstvo; Historical survey; Zgodovinski pregled; literarna besedila; literarni slogi